Characterization of exotic oil palm germplasm using IBPGR descriptors and identification of promising genetic stocks - Murugesan, P.; Somasundaram, G.; Pedapati, Anitha; Sunil Kumar, K.; Rahana, S. N.; Bhagya, H. P.; Ramajeyam, D.; Ravichandran, G.; Mathur, R. K. (Journal of Plantation Crops, 2026)
Oil palm (Elaeis guineensis Jacq.) improvement depends on the availability and effective utilization of genetically diverse germplasm. The present study aimed to characterize 24 selected oil palm germplasm accessions maintained at ICAR–Indian Institute of Oil Palm Research, which included Elaeis guineensis (17 duras and 2 teneras) and Elaeis oleifera (5 accessions), using IBPGR (1989) descriptors and to identify palms with economically important traits. The accessions represented diverse geographic origins from Africa, South America, and Southeast Asia. Considerable variability was recorded for tree form, fruit form, bunch traits, bunch quality components, and vegetative characters. Dura and tenera fruit forms were observed in Elaeis guineensis, with predominance of dura, while E. oleifera exhibited thick-shelled fruits. Bunch weight ranged from 3.76 to 44.01 kg, while oil to bunch varied from 5.70 to 21.50%. Palm height ranged from 2.2 to 9.0 m, indicating the presence of both compact and tall palms. Based on trait-specific performance for bunch traits, bunch components, and vegetative characteristics, palms viz., DOPR-G23 (O6), DOPR-G24 (O22), DOPR G53 (E.61), and DOPR-G59 (E.48) were identified as potential parental sources for utilisation in breeding programmes, being superior for high bunch weight, high fruit to bunch, high oil to bunch, and low shell to fruit, respectively.